Acts and sustainable events in the most responsible organizations in Spain: Follow-up of the ISO 20121 criteria in the events of the leading companies in the MERCO ranking - Sánchez-Hervás, David; Hernández Martínez, Salvador (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The objective of this research focuses on observing the events organized by the most responsible companies according to the MERCO ranking, taking into account whether they meet the sustainability characteristics defined by ISO 20121 on event sustainability management systems, which are: inclusivity, integrity, responsibility and transparency. To do this, all events will be analyzed, paying special attention to those specifically considered sustainable. The results show that less than half follow sustainability criteria in their realization. It is striking that the ISO 20121 Standard is hardly applied in the most responsible organizations in Spain.